Missing persons of post-conflict countries: Assessing dental identification through a questionnaire-based study in Syria - Rawad Qaq; Scheila Mânica; Sean McAleer (Forensic Science International: Reports)
Locating and identifying missing persons is crucial to protecting human rights and rebuilding war-torn countries like Syria. Biological identity primarily relies on DNA, fingerprints, or dentition. However, post-conflict countries with high deaths, limited databases, insufficient resources, and a reduced or a lack of forensic expertise make this effort more challenging. Teeth are a practical and cost-effective means to identify human remains, particularly when acceptable dental records are available. Still, the application of comparative dental analysis in conflict scenarios needs to be more explored.A survey study in Syria examined whether post-conflict countries could employ comparative dental identification of missing individuals. The attitudes and perceptions of four groups (the public and dentists, forensic odontologists, dental schools, and the Syrian Dental Association) were determined using questionnaires and analysed for the first two groups. Most respondents (>90 %) indicated that addressing disappearance is crucial for post-conflict reconstruction and considered it unachievable without international support and only 20 % had confidence in this support. Issues hindering human identification reported by a high percentage of dentists and forensic odontologists and included education in Forensic Odontology (92 %), expertise in the field (70 %), awareness (90 %), the availability of antemortem records (92.3 %) and political and security influence (50 %). Responses from over 80 % of the public, 50 % of the dentists and 92 % of the forensic odontologists indicated that comparative dental identification in Syria may not be feasible.The results of this study provide strong evidence of the challenges in identifying missing persons using teeth in developing nations, particularly those affected by conflicts. They include the lack of antemortem records and forensic expertise. The international community is urged to support post-conflict nations including Syria.